Autism, advocacy organizations, and past injustice - Rosenblatt, Adam (Brazilian Journal of Implantology and Health Sciences, 2022)
Fruitful connections can be made between Disability Studies and post-conflict transitional justice, two areas of scholarship concerned with human rights and the impacts of violence that have rarely been brought into critical dialogue with one another. For over a decade, one of the world’s largest and best-known autism organizations, the US-based Autism Speaks, has been subject to criticisms and boycotts by autistic self-advocates and their allies. This article describes the forms of harm attributed to the organization, arguing that these harms can be viewed through the lens of what transitional justice scholar Jill Stauffer calls "ethical loneliness": "the experience of being abandoned by humanity compounded by the experience of not being heard" (2015b, 1). I argue that Autism Speaks’s recent reforms and responses to criticism, in focusing largely on present-day organizational policies and structures, fail to grasp the full temporal dimensions of ethical loneliness or the importance of addressing past injustice.